Corrosion effect on reinforced concrete with the addition of graphite powder and its evaluation on physical-electrochemical properties - Flores-Nicolás, Alejandro; Flores-Nicolás, Mario; Uruchurtu-ChavarínJorge (Revista ALCONPAT, 2021)
The corrosion of reinforced concrete without and with the addition of graphite powder with low carbon content was evaluated. Phase identification processes and physical-electrochemical properties of the concrete were analyzed using X-ray diffraction techniques (XRD), scanning electron microscopy (SEM), half-cell potential, electrochemical noise (EN) and linear polarization resistance (LPR). Samples were studied for 168 days in saline solution. The results show that, when adding graphite powder in an amount of 2.5% by weight of cement, the compressive strength increased if compared with the control sample. The electrochemical tests show that the higher the level of graphite replacement, the higher the level of corrosion in concrete.